Faktor-Faktor yang Berhubungan dengan Kejadian Diabetes Melitus (DM) di Desa Kubah Sentang Kecamatan Pantai Labu - Salsabila Ainul Muna Lubis; Tiara Novia Fajar Aminah; Sashi Pangestuty; Rahmi Atika; Sandi Pranata Sembiring; Zuhrina Aidha (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Analyze the risk factors associated with the incidence of Diabetes Mellitus in the village of Kubah Sentang, Pantai Labu subdistrict. This type of research is quantitative descriptive with a cross sectional research design. The sample in this study were all respondents who were diagnosed with Diabetes Mellitus. Consists of a case sample of 30 people. The factors associated with the incidence of diabetes mellitus are gender, education and hypertension with the incidence of Diabetes Mellitus in residents in the village of Kubah Sentang, Pantai Labu District. The factors that are not related to the incidence of diabetes mellitus are smoking and obesity which have no association with the incidence of DM in the village of Dome Sentang. Occupational status and physical relationships are factors that can affect the risk of diabetes mellitus in Kubah Sentang Village, Pantai Labu District. Physical activity such as exercise is an important part of health in terms of disease prevention. Exercise habits do not greatly affect the decrease in blood sugar but can increase glucose oxidation which can reduce insulin in people with diabetes mellitus. Good exercise will be useful in regulating blood glucose levels in people with diabetes mellitus which will affect the control of blood sugar levels.